2006
DOI: 10.1002/chem.200501280
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Theoretical Studies of Magnetic Exchange in Silole‐Bridged Diradicals

Abstract: Five bis(tert-butylnitroxide) diradicals connected by a silole (7 a-d) or a thiophene (12) ring as a coupler were studied. Compound 12 crystallizes in the orthorhombic space group Pna2(1) with a = 20.752(5), b = 5.826(5), and c = 34.309(5) A. X-ray crystal structure determination, electronic spectroscopy, variable-temperature EPR spectroscopy, SQUID measurements and DFT computations (UB3LYP/6-31+G*) were used to study the molecular conformations and electronic spin coupling in this series of molecules. Whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
1
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 73 publications
4
12
1
3
Order By: Relevance
“…A diluted solution of polymorph I in C 6 D 6 shows six hyperfine lines (see the Supporting Information). The signal broadens on cooling to 200 K. [12] The EPR intensities of both the solution and the solid phase plotted against T À1 follow straight lines where the signal intensity increases with decreasing temperature, thus indicating very weak interactions between two spins in polymorph I of 2. Since polymorph II is diamagnetic in the temperature range of 300-2 K, it is EPR silent.…”
Section: CLmentioning
confidence: 92%
See 3 more Smart Citations
“…A diluted solution of polymorph I in C 6 D 6 shows six hyperfine lines (see the Supporting Information). The signal broadens on cooling to 200 K. [12] The EPR intensities of both the solution and the solid phase plotted against T À1 follow straight lines where the signal intensity increases with decreasing temperature, thus indicating very weak interactions between two spins in polymorph I of 2. Since polymorph II is diamagnetic in the temperature range of 300-2 K, it is EPR silent.…”
Section: CLmentioning
confidence: 92%
“…Power [8] and Lee et al reviewed persistent stable free radicals of Group 14. [9] Grützmacher et al [10] reported on radicals of main-group elements, Rajca et al [11] described singlet-triplet bistability and Roques et al [12] investigated the exchange in silole-bridged biradicals. Neese et al [13] studied the interaction of radical pairs through bonds and through space.…”
Section: Dedicated To Professor Heribert Offermanns On the Occasion Omentioning
confidence: 99%
See 2 more Smart Citations
“…Grützmacher et al [10] berichteten über Radikale von Hauptgruppenelementen. Rajca et al [11] beschrieben Singulett-Triplett-Bistabilitäten und Roques et al [12] untersuchten den Austausch in silolverbrückten Biradikalen. Studien über die Bindungs-und Raumwechselwirkungen zwischen Radikalpaaren wurden von Neese et al [13] verçffentlicht.…”
unclassified